West Coastal Toponyms of Sumatra Island: A Corpus Linguistics Study - Hetti Waluati Triana; Martin Kustati; Nelmawarni Nelmawarni; Reflinaldi Reflinaldi (IAIN MADURA, 2022)
Several pieces of research on the toponym of place names in Indonesia have been carried out but focus on place names on the island of Java. The limited documentation of place names makes the study of toponymy in Sumatra a must. This article aims to map the thematization of place naming on the West Coast of Sumatra Island. The research was conducted in a qualitative descriptive manner with a corpus linguistic approach. Data was collected by means of documentation, interviews, and focus group discussions. Data were analyzed by following work procedures by Miles and Huberman (2013), involving data condensation, data display, verification drawing, and Sudaryat's toponymy categorization (2009). The results showed that the toponym of place names on the West Coast of Sumatra Island reflects the relationship between humans and their natural environment. This relationship is manifested through the thematization of place names, namely: embodiment, social, and culture. The embodiment aspect includes the sub-themes of water background, topographical background, and natural environment background. The social aspects include the sub-themes of residential background, economic activity background, and building background. The cultural aspects include sub-themes of myths, folklore, and legends passed down through oral traditions.